IMPLEMENTASI TANDUR TERHADAP KETERAMPILAN BERBICARA SISWA KELAS V SEKOLAH DASAR NEGERI 05 PONTIANAK KOTA - Muhsinin, Muhsinin; Marzuki, Marzuki; Halidjah, Siti (Jurnal Pendidikan dan Pembelajaran Khatulistiwa, 2019)
AbstractThis study aims to describe the effect of implementation TANDUR towards speaking skills of 5th grade in elementary school. Form of the research used was pre-experimental design with the design of one-group pretest-postest design. The population of the research was the whole 5th grade SD Negeri 05 Pontianak Kota that consist of VA and VB class. Sampling technique that is used is the probability sampling technique and the type of sampling techniques used are simple random sampling. VB class was chosen as the sample of research with 21 students. Data collection tools is a test of speaking skills in the form of reserved essays and commands. Based on statistical calculation, from the average of the results of the experimental class posttest 72.50 obtained thitung of 8.45 and ttabel (Î± = 5%) amounted to 1.725, it meant that thitung > ttabel (8.45 > 1.725), and Ha is received. So, it can be explained that there is a difference between the students speaking skills before and after given the treatment with TANDUR implementation. From the calculation of effect size, gained 1.76 (high criteria), which means that the TANDUR learning framework is give a high effect towards the speaking skills of 5th grade SD Negeri 05 Pontianak Kota in commenting on the factual problem.Â Keywords: Implementation, TANDUR, Speaking SkillsÂ